TRANSFORMASI DIGITAL, PERUBAHAN SOSIAL DAN TANTANGAN REPRODUKSI BUDAYA DAMAI MASYARAKAT AGAMA DI YOGYAKARTA - Mohammad Iqbal Ahnaf; Yulianti; Selvone Christin Pattiserlihun; M Naufal Firosa Ahda (Jurnal Masyarakat dan Budaya, 2023)
Social change and digitalization influence people's lives, especially in socializing. Social change and digitization can impact society’s integrity, especially in the conditions of peace that exist in the life of religious communities. This study aims to know and understand how society produces a culture of peace in the challenges of digitalization and social change that exist. The method used qualitative with a case study approach. collecting data using focus group discussion (FGD) deep interview techniques, observation, and literature studies. The subjects used in this study were twenty-one people who came from backgrounds such as citizens, youth, women, community leaders, and religious figures. The subjects came from three villages and were spread across two areas of Yogyakarta Province, Sleman and Kulonprogo. The results show that the people in the three villages have their way of producing a culture of peace. The culture of peace in the three villages manifests in several community activities such as village traditions, religious ceremonies, and daily activities. In addition, social changes and the impact of digitalization show indications that the space for encounters, especially for young people and other residents, has shifted due to the massive influence of digitalization. Therefore, the resulting impact will affect community relations in the three villages.